From bio-waste to bone substitute : synthesis of biomimetic hydroxyapatite and its use in chitosan-based composite scaffold preparation - Ressler, Antonia (Array, 2020)
Nanocomposite structure of the bone can be mimicked by chitosan/hydroxyapatite (CS/HAp) composite scaffold. Biological hydroxyapatite (HAp) contains various ions, which have a crucial role in bone growth. The aim of the present work was to synthesize biomimetic hydroxyapatite and prepare composite scaffolds based on chitosan, where HAp was synthesised from hen eggshells, seashells and cuttlefish bone. The powders were composed of nano-structured calcium deficient HAp and amorphous calcium phosphate (ACP). In the as-prepared powders, Sr2+, Mg2+ and Na+ ions were detected as a result of using biogenic precursor of Ca2+ ions. Highly porous CS/HAp structures have been prepared by freeze-gelation technique. The CS/HAp scaffolds have shown highly porous structure with very well interconnected pores and homogeneously dispersed HAp particles. The MTT assay of CS/HAp scaffolds has shown no toxicity, and the live/dead assay has confirmed good viability and proliferation of seeded cells.